Phytochemical Screening and In-Vitro Antioxidant Activities of Various Extracts of Helichrysum petiolare Hilliard & B.L. Burtt used for the Treatment of Diabetes Mellitus in the Eastern Cape Province of South Africa - Adebowale Emmanuel Aladejana; Graeme Bradley; Anthony Jide Afolayan (Journal of Pharmacy and Nutrition Sciences, 2020)
The phytochemical contents of the acetone, ethanol, and boiled and cold aqueous whole-plant extracts of Helichrysum petiolare were determined using standard phytochemical reaction methods. ABTS, DPPH, NO and TAC assays were used to evaluate their antioxidant properties. This study reported the highest total phenolic content (212,963 mg/g) in the boiled aqueous extract, while the ethanol had the highest flavonoid (172.393 mg/g) and proanthocyanidin contents (65.855 mg/g). Alkaloids, flavonols, and saponin were highest in the acetone extract, while the cold aqueous extract had the lowest phytochemical content. Among the extracts, the boiled aqueous extract had the highest DPPH•+ (IC50 0.02 mg/mL) and ABTS•+ (IC50 0.07) inhibition capacities, while the ethanol extract exhibited the highest NO• Inhibition (IC50 0.41 mg/mL) and TAC (IC50 0.19 mg/mL). These findings justify the use of H. petiolare in traditional medicine and further recommend the ethanol and boiled aqueous extracts of the plant as more effective extracts for medicinal treatment.